CASE STUDY DECISION OF PEMATANG SIANTAR STATE COURT NUMBER 288/PID.B/2020/PN PMS REGARDING MURDER COMMITTED BY HALLUCINATION SUFFERERS - Nurhafifah Nurhafifah; Fadila Jamiatul Husna (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2022)
The decision 288/Pid.B/2020/PN Pms of the Pematang Siantar District Court on the murder committed by a psychotic schizophrenic (hallucinations). In this ruling, the judge concluded that the defendant, Suheri Sihombing, had been lawfully and conclusively established to have violated Section 338 of the Criminal Code, committing the crime of murder. Even though the defendant has paranoid schizophrenia, the judge believes he can still be held accountable for his conduct, therefore he is sentenced to thirteen years in jail. The findings indicate that the judge in case 288/Pid.B/2020/PN Pms did not consider the trial's facts when rendering a verdict. The judge did not voice his thoughts on the defendant with paranoid schizophrenic mental disease. The judge did not give significant consideration to Article 44, paragraph 1, of the Criminal Code concerning criminal abolition. According to Article 44 of the Criminal Code, defendants with mental problems might be ordered to spend one year in a mental hospital. The panel of judges at the Pematang Siantar District Court found the defendant guilty, resulting in a decision that did not maximally satisfy the norm of legal fairness.